2019
DOI: 10.1096/fj.201901061r
|View full text |Cite
|
Sign up to set email alerts
|

Butyrolactone‐I, an efficient α‐glucosidase inhibitor, improves type 2 diabetes with potent TNF‐α–lowering properties through modulating gut microbiota in db/db mice

Abstract: The aim of this study was to evaluate the effects of butyrolactone‐I (A6) on type 2 diabetes (T2D) in db/db mice because A6 was found to inhibit α‐glucosidase activities and TNF‐α release, which were associated with improving T2D. Male db/db mice were divided into 6 groups and given an equivalent volume of olive oil, acarbose, or different doses of A6 for 4 wk (n = 8/group). In this study, 11 butenolide derivatives were screened for their α‐glucosidase and TNF‐α suppressive activity in vitro. A6, an efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…However, BTL-1 has different activities in the IBD mouse model, which inhibits the phosphorylation of ERK and P38, thus downregulating the expression of TNF-α. Our results are consistent with the results of related literature in inhibiting the expression of TNF-α in mice (46).…”
Section: Discussionsupporting
confidence: 94%
“…However, BTL-1 has different activities in the IBD mouse model, which inhibits the phosphorylation of ERK and P38, thus downregulating the expression of TNF-α. Our results are consistent with the results of related literature in inhibiting the expression of TNF-α in mice (46).…”
Section: Discussionsupporting
confidence: 94%
“…Lipopolysaccharide (LPS) in the blood circulation forms a complex with CD14 of monocyte macrophages, which is recognized by toll-like receptor 4 (TLR4) on the surface of immune cells. They could activate nuclear transcription factors through myeloid differentiation molecule 88 (MyD88) [ 3 ] and promote the synthesis and secretion of many inflammatory factors including tumor necrosis factor α, interferon γ, and interleukin-6, which may further affect the insulin resistance and T2DM [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, AGIs are reported to increase the levels of butyrate, which is associated with the inhibited growth of transformed cells in the colorectal mucosa [17] and the inhibition of the production and activity of bile acids, particularly secondary bile acids, which are said to have carcinogenic effects owing to weak acidification of the intestinal environment. Moreover, many studies have indicated the links between gut microbiota and CRC development [44], and recent investigations have shown that AGI may attenuate inflammation and ameliorate DM through modulating intestinal microbiota [45,46]. Those effects of AGIs might be associated with suppression of CRC development, although bile acid metabolism or alteration of gut microbiota were not examined in this study.…”
Section: Discussionmentioning
confidence: 90%